LIFE FORM OF TUBERCULOSIS PATHOGEN AND ITS TOXIC EFFECTS ON THE ORGANISM (INTERNATIONAL CONFERENCE ON INTERDISCIPLINARY SCIENCE, 2026)
Tuberculosis (TB) remains a global health problem due to its high infectivity, high mortality rates, and the complexity of its treatment. It spreads through airborne droplets and affects not only the lungs but also other organs. The disease causes more than 1.6 million deaths annually and requires a specialized drug course lasting several months for treatment. According to the World Health Organization (WHO), millions of new cases of tuberculosis are recorded worldwide every year.